2000
DOI: 10.1042/bj3520865
|View full text |Cite
|
Sign up to set email alerts
|

Control of pancreatic bile-salt-dependent-lipase secretion by the glucose-regulated protein of 94kDa (Grp94)

Abstract: Bile-salt-dependent lipase (BSDL ; EC 3.1.1.13) is an enzyme expressed by the pancreatic acinar cell and secreted as a component of the pancreatic juice. During its route towards secretion, BSDL is associated with intracellular membranes by means of a multiprotein folding complex, which includes the glucose-regulated protein of 94 kDa (Grp94). We have postulated that the association of BSDL with membranes is required for the complete O-glycosylation of the protein, which diverts BSDL from a degradation route a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 54 publications
(76 reference statements)
0
10
0
Order By: Relevance
“…Such methodology is limited by the possibility that observed effects consecutive to amino acid substitution could be the result of an altered enzyme structure leading to a loss of function. This may not be the case as the mutagenized enzyme is normally secreted, whereas we have shown previously (20,21) that the unfolded or incorrectly folded BSDL is directed toward the ubiquitination and proteasome degradation pathway instead of the secretion route. Furthermore, the wild-type and mutagenized enzymes are still active to the same level on soluble substrates in the absence of activating bile salts.…”
Section: Fig 4 Secretion Of Y427s and Y453s Mutagenized Bsdl By Tramentioning
confidence: 68%
See 1 more Smart Citation
“…Such methodology is limited by the possibility that observed effects consecutive to amino acid substitution could be the result of an altered enzyme structure leading to a loss of function. This may not be the case as the mutagenized enzyme is normally secreted, whereas we have shown previously (20,21) that the unfolded or incorrectly folded BSDL is directed toward the ubiquitination and proteasome degradation pathway instead of the secretion route. Furthermore, the wild-type and mutagenized enzymes are still active to the same level on soluble substrates in the absence of activating bile salts.…”
Section: Fig 4 Secretion Of Y427s and Y453s Mutagenized Bsdl By Tramentioning
confidence: 68%
“…Those data suggest that substitutions significantly affect the enzyme activity on 4-NPC when recorded in the presence of activating concentrations of bile salt (4 mM NaTC). We have shown that unfolded BSDL cannot be secreted and instead is degraded by the proteasome (20,21). No degradation product can be detected on Western blotting performed on MC9 clone lysates (not shown).…”
Section: Resultsmentioning
confidence: 99%
“…Opposite to mAb16D10, the mAbJ28 recognizes pancreatic tumor, but it has no effect on tumor growth. 8 Therefore, mAb16D10 could be of interest as therapeutic agents for passive immunization as described for breast cancers (48), provided that these antibodies specifically recognize human pancreatic tumoral tissues in vivo. Moreover, we have shown that the 16D10 antigen was expressed in metastatic pancreatic tumor and in tumor from patient after a preoperative chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Antibodies The patented IgM mAb16D10 directed against O-glycosylated repeated COOH-terminal mucin domain of FAPP (23), the patented IgG mAb8H8 against BSDL, 8 and the polyclonal antibodies (pAb) L64 against BSDL/FAPP (17) were homemade. mAbJ28 specific for the fucosylated J28 glycotope carried by repeated COOH-terminal sequences of FAPP was a generous gift from Dr. M-J.…”
Section: Humantissuesmentioning
confidence: 99%
See 1 more Smart Citation